Education for tomorrow: The vision of Rabindranath Tagore - Quayum, Mohammad Abdul (Routledge, 2016)
This article investigates Rabindranath Tagore’s educational vision, which underpinned the three institutions he set up in India – Santiniketan (1901), Visva-Bharati (1921) and Sriniketan (1922). It argues that this vision is still relevant for the world of today and tomorrow, and that it should be taken into account in designing any educational model for the future. Tagore rejected the modern mechanical learning that focuses merely on cultivation of the individual’s mind, in favour of learning that encourages the creativity, imagination and moral awareness of students. He believed that education should be not for mere “success” or “progress” but for “illumination of heart” and for inculcation of a spirit of sympathy, service and self-sacrifice in the individual, so that s/he could rise above egocentrism and ethnocentrism to a state of global consciousness or worldcentrism. In pursuing this argument, I refer to Tagore’s letters, lectures, interviews and essays, both in Bengali and in English, a body of his short stories, his novel The Home and the World and his allegorical poem “Two Birds”. I also explain his awareness of the educational movements of his time in the West, and draw brief parallels with selected Western luminaries in the field, such as Plato, Montaigne, Rousseau and John Dewey. My contention is that although some may dismiss Tagore’s educational principles as “rickety sentimentalism” in a world that is palpable and real, his ideas of human fellowship, unity and creativity, and kinship for nature seem irrefutable with the rise of multiculturalism and the looming ecological crisis threatening world peace.